The Future of Animation: Exploring the Integration of Generative AI and the Role of Animators - Troy; Gunanto, Samuel Gandang (Journal of Information Technology and Its Utilization, 2025)
Artificial Intelligence (AI) capabilities significantly change the way creative actors in the production process work. Through a study of the impact of AI on the animation industry, this article highlights the shift of AI from basic automation to more complex roles. Multi-modal generative AI, such as Large Language Models (LLMs) and diffusion models, revolutionizes the animation workflow, changes the job description of animators, and creates new challenges and opportunities. The analysis is carried out on repetitive tasks such as in-betweening, rendering, and asset creation. Through the exploration of the application of diffusion models for the creation of image and video works, as well as the application of LLMs in the development of narratives and storyboards, animators are expected to focus more on conceptual aspects and increase their creativity. AI will be involved as an innovative partner. This partnership encourages various forms of new creative expression as well as collaborative and integrated workflows. It is undeniable that this leaves notes and challenges related to the potential shift in human resources and ethics. This article provides an explanation of the adaptations that must be made so that the integration of technology and humans can maximize human creativity, not to replace it.